The past and current role of pupil’s effort and physical tests in Norwegian physical education teacher’s assessment - Tremoen, Tora; Sørensen, Arne; Lagestad, Pål (Frontiers in Education, 2024)
Assessment practice is an important part of a physical education (PE) teachers work and can contribute positively to motivating pupils towards learning and developing lifelong pleasure in movement. In 2020, a new curriculum, “the Knowledge Promotion” 2020 (LK20) was introduced in Norwegian schools. This study aims to investigate physical education teachers’ assessment practice relating to the view of effort and testing in PE, after the introduction of LK20. Nine in depth interviews were conducted with nine PE teachers from seven upper secondary schools in Norway. The data were analyzed using NVivo 12 and meaning condensation. The findings show that the informants use effort differently and to a greater extent related to pupil using their skills to help fellow pupils improve. Furthermore, the informants experience effort as a greater and more important part of the assessment with LK20, than with the previous curriculum. Furthermore, the analysis suggests that the use of physical tests may have decreased. The findings indicate that there has been a change in the informants’ assessment practice in line with the curriculum’s intention, with less focus on skills and more on effort. However, the findings indicates that PE teachers have much freedom in their assessment, and points towards a need for more follow-up and professional development for PE teachers.